(untitled) (Research, Society and Development, 2020)
Objective: To identify the level of knowledge of students of the Dentistry Course at the Federal University of Campina Grande, campus of Patos, regarding dental autotransplantation as a treatment for oral rehabilitation. Methods: This was a cross-sectional, observational study, with an inductive, descriptive approach, adopting a specific questionnaire as a strategy for data collection, applied to 143 graduates regularly enrolled from the 5th to the 10th period of the dentistry course, between the year 2019 and 2020. Aspects covered: characterization of students and information related to dental autotransplantation (concept, indications, contraindications and factors that influence the success of treatment). Results: Most of the interviewees were female. There was a satisfactory level of knowledge about the indications, contraindications, advantages and the need for no loading of the self-transplanted tooth. Conclusion: Despite not being a common procedure in clinical practice and dental education, within the methodology used in this study, it was possible to observe a satisfactory level of knowledge among dentistry students at UFCG, Patos-Paraíba about dental autotransplantation.